Analysis of the Sharia Management Accounting System as the Main Driver for Sustained Sharia Financial Inclusion - Muammar Khaddafi; Cheren Putri; Ainun Marziah; Dilla Amanda; Nurul Husna; Widodo Widodo (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Financial literacy and inclusion and formulate recommendations to optimize its contribution in increasing sharia financial inclusion in Indonesia. The data collection technique used is analyzing the data by means of describe or describe the collected data that is generally applicable or a generalization. From the results of this research, it can be concluded that the 2022 SNLIK data shows a significant increase in the sharia financial literacy and inclusion index. Literacy increased from 8.93% (2019) to 9.14% (2022), while inclusion increased from 9.10% to 12.12%. This increase reflects positive efforts to increase public understanding and participation in sharia financial inclusion.